Surface processes forcing on extensional rock melting - Sternai, Pietro (Sci Rep, 2020)
Surface processes and magmatism condition the structural evolution of continental rifts and passive margins through mechanical and thermal effects on the lithosphere rheology. However, their inter-relationships in extensional settings are largely unknown. Here, I use coupled thermo-mechanical geodynamic and landscape evolution numerical modeling to assess the links between erosion of rift shoulders, sedimentation within the rift basin and extensional rock melting. Results suggest that, when the crust is thinner than ~40 km, the extension rate is slower than ~2 cm/yr and the mantle potential temperature is below ~1230 °C, efficient surface processes may double crustal melting by Moho lowering and inhibit mantle decompression melting by ~50% through sediment loading within the rift basin. It is thus likely that surface processes significantly influenced the magmatic activity of a number of extensional settings worldwide – e.g. the Mediterranean, the Gulf of California, the Iberia-Newfoundland margin, and the South China Sea. Because magmatism and surface processes affect jointly the geological carbon cycle, the surface processes forcing on extensional rock melting investigated here involves an additional means of linkage between plate tectonics and climate changes.